PENGARUH FASILITAS KANTOR DAN KOMPETENSI TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KANTOR DINAS LINGKUNGAN HIDUP KABUPATEN BANGGAI - Saudin, La; Polim, Adrian (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The aim of this research is to find out whether office facilities and competencies partially and simultaneously have a positive and significant effect on work effectiveness at the Banggai Regency Environmental Service Office. The research sample is all employees at the Banggai Regency Environmental Service Office using a purpose sampling technique with a total of 48 people. Data collection methods use interviews and questionnaires. Data were analyzed quantitatively descriptively using frequency tables and multiple linear regression with 2 predictors. Results of data processing carried out using the SPSS version 25.0 program. From the results of the t test, it was found that all independent variables, namely Office Facilities (X1) and Competence (X2), had a partial influence on Work Effectiveness (Y) at the Banggai Regency Environmental Service Office. From the results of the ANOVA (analysis of variance) test or F test, it was found that F-count was 299.526 and F-table was 3.23. With this comparison, it means that it can be seen that F-count = 299.526 > F-table = 3.23, which means simultaneously positive and significant effect. The partial research results show that Competence is the variable that has the most dominant and significant influence with a coefficient value of 1.085, which means that Competency has an influence on Work Effectiveness (Y)